Ocorrência em cultivares e controle químico de lagartas, ácaros e tripes, em soja - Demarco, Liamar (2013)
The soybean crop is affected by numerous problems during its development. There are several species of insect pests that cause damage, reducing the crop yield. Two experiments were conducted in randomized block design, four replicates, during November 2011 to April 2012, at University of Passo Fundo. The objective of the first experiment was to evaluate the occurrence and frequency of pests in 14 soybean cultivars (treatments) emphasizing the infestation differences between them. The second, using only cv. BMX Apolo RR, it was evaluated three insecticides formulations compared to two controls (without insecticide and with insecticide systematic application) regarding pest control and effect on predators. In both experiments it was evaluated defoliation and insect-pests and natural enemies’ densities. In the second experiment the plots were harvested for yield and economic analysis. The data were transformed into square root, except the yield and yield components, and subjected to analysis of variance at 5% significance level. The means were compared by the Scott Knott test (first experiment), and by Tukey (second experiment). The occurance of velvetbean caterpillar (Anticarsia gemmatalis), spider mites (Tetranychus urticae e Tetranychus spp.) and thrips (Caliothrips phaseoli e Frankliniella schultzei) vary according to the cultivar. In conditions of high infestation and dry season, chemical control of thrips and spider mites prevents the reduction in soybean grain yield. The economic result of the use of insecticides and/or acaricides in soybean depends on the product (price and effectiveness) and the insect-pests that occur on level to cause damage.